Analisis Implementasi Pengelolaan Keuangan Desa di Desa Modo - Rahmadani Raukang; Rio Monoarfa; Mahdalena (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the implementation of Village financial management in Modo Village which includes the Planning, Implementation, Administration, Reporting and Accountability stages because there are indications that village financial management is not in accordance with Minister of Home Affairs Regulation Number 20 of 2018. The data analysis used in this research is a descriptive qualitative approach. Data collection methods were carried out by means of observation, interviews and documentation. Data validity testing was carried out using triangulation techniques. The research location is in Modo Village, Bukal District, Buol Regency. The results of this research indicate that financial management in Modo Village has been carried out based on Minister of Home Affairs Regulation Number 20 of 2018. In its implementation, financial management in Modo Village at the administration and accountability stage has not been in accordance with Minister of Home Affairs Regulation Number 20 of 2018. However, at this stage planning, implementation and reporting are in accordance with Minister of Home Affairs Regulation Number 20 of 2018.